2017
DOI: 10.1073/pnas.1610223114
|View full text |Cite
|
Sign up to set email alerts
|

The nonreceptor tyrosine kinase c-Src attenuates SCF(β-TrCP) E3-ligase activity abrogating Taz proteasomal degradation

Abstract: The polyomavirus middle T antigen (PyMT) oncogene activates the cellular nonreceptor tyrosine kinase c-Src and recruits the Hippo pathway effectors, Yap (yes-associated protein) and Taz (transcriptional coactivator with PDZ-binding motif), as key steps in oncogenesis. Yap and Taz are transcription coactivators shuttling from the cytoplasm to the nucleus. The Hippo pathway kinase Lats1/2 (large tumor suppressor homolog) reduces Yap/Taz nuclear localization and minimizes their cytoplasmic levels by facilitating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 34 publications
1
33
0
Order By: Relevance
“…Phosphorylation of serine (S) 127 and S397 was stimulated by TFCP2 knockdown ( Figure S4F), further supporting the hypothesis that TFCP2 overexpression suppresses bTrCP binding to YAP. After ubiquitination by bTrCP, YAP is degraded in the cytoplasm (Shanzer et al, 2017). However, nuclear accumulation of YAP was dosedependently stimulated by TFCP2 overexpression and inhibited by TFCP2 knockdown (Figures S4G and S4H), suggesting that TFCP2 prevents YAP from shuttling between the nucleus and cytoplasm.…”
Section: Tfcp2 Prolongs the Half-life And Reduces Ubiquitination Of Ymentioning
confidence: 97%
“…Phosphorylation of serine (S) 127 and S397 was stimulated by TFCP2 knockdown ( Figure S4F), further supporting the hypothesis that TFCP2 overexpression suppresses bTrCP binding to YAP. After ubiquitination by bTrCP, YAP is degraded in the cytoplasm (Shanzer et al, 2017). However, nuclear accumulation of YAP was dosedependently stimulated by TFCP2 overexpression and inhibited by TFCP2 knockdown (Figures S4G and S4H), suggesting that TFCP2 prevents YAP from shuttling between the nucleus and cytoplasm.…”
Section: Tfcp2 Prolongs the Half-life And Reduces Ubiquitination Of Ymentioning
confidence: 97%
“…[ 179 ] Tumor cells interact with the ECM via Integrins, which respond to ligand binding and mechanical stress by signaling through FAK and SRC family kinases [ 180–182 ] to inhibit Hippo signaling and activate YAP/TAZ. [ 31,61,183‐199 ] SRC family kinases appear to act primarily by direct tyrosine phosphorylation of LATS1, but can also directly phosphorylate YAP/TAZ. [ 30,31,61,183‐199 ] Importantly, there is extensive signaling cross‐talk between Integrin‐SRC signaling and Growth factor‐PI3K‐Akt signaling.…”
Section: Introductionmentioning
confidence: 99%
“…[ 31,61,183‐199 ] SRC family kinases appear to act primarily by direct tyrosine phosphorylation of LATS1, but can also directly phosphorylate YAP/TAZ. [ 30,31,61,183‐199 ] Importantly, there is extensive signaling cross‐talk between Integrin‐SRC signaling and Growth factor‐PI3K‐Akt signaling. [ 200–206 ] In addition, mechanotransduction via Integrin‐SRC signaling also promotes formation of focal adhesions and stress fibers, a process involving increased Rho GTPase mediated actomyosin contractility.…”
Section: Introductionmentioning
confidence: 99%
“…However, we did not acquire any direct evidence to precisely show how NUSAP1 promotes the translocation of YAP to the nucleus. Previous studies have shown that the recruitment of β-TrCP ubiquitin ligase to the C-terminal region of YAP facilitates its ubiquitination and degradation [44]. We suspect that NUSAP1 interacts with the C-terminal region of YAP, preventing it from being ubiquitinated by β-TrCP ligase, thus leading to YAP stabilization and activation.…”
Section: Discussionmentioning
confidence: 85%